Thermal and Solvent Stress Cross-Tolerance Conferred to Corynebacterium glutamicum by Adaptive Laboratory Evolution - Oide, Shinichi (Appl Environ Microbiol, 2015)
Reinforcing microbial thermotolerance is a strategy to enable fermentation with flexible temperature settings and thereby to save cooling costs. Here, we report on adaptive laboratory evolution (ALE) of the amino acid-producing bacterium Corynebacterium glutamicum under thermal stress. After 65 days of serial passage of the transgenic strain GLY3, in which the glycolytic pathway is optimized for alanine production under oxygen deprivation, three strains adapted to supraoptimal temperatures were isolated, and all the mutations they acquired were identified by whole-genome resequencing. Of the 21 mutations common to the three strains, one large deletion and two missense mutations were found to promote growth of the parental strain under thermal stress. Additive effects on thermotolerance were observed among these mutations, and the combination of the deletion with the missense mutation on otsA, encoding a trehalose-6-phosphate synthase, allowed the parental strain to overcome the upper limit of growth temperature. Surprisingly, the three evolved strains acquired cross-tolerance for isobutanol, which turned out to be partly attributable to the genomic deletion associated with the enhanced thermotolerance. The deletion involved loss of two transgenes, pfk and pyk, encoding the glycolytic enzymes, in addition to six native genes, and elimination of the transgenes, but not the native genes, was shown to account for the positive effects on thermal and solvent stress tolerance, implying a link between energy-producing metabolism and bacterial stress tolerance. Overall, the present study provides evidence that ALE can be a powerful tool to refine the phenotype of C. glutamicum and to investigate the molecular bases of stress tolerance.